Primary Aldosteronism at Prapokklao Hospital - Takkavatakarn, Pratarn; Polamaung, Waraporn (Chulalongkorn Medical Journal, 2023)
Background : Primary aldosteronism (PA) is a cause of secondary hypertension which characterized by hypertension, increased plasma aldosterone concentration (PAC), and suppressed plasma renin activity (PRA). Objective : To study the prevalence of primary aldosteronism and clinical clue for diagnosis of PA. Setting : Prapokklao Hospital, Chanthaburi Province. Materials and Methods : All patients whose diagnoses of primary aldosteronism from October 2006 - March 2012 were reviewed. Results : The prevalence of PA at Prapokklao Hospital was 0.15% (20 cases of PA) of HT. 70% of cases were female. The age at the diagnosis of HT ranged from 32.58 to 72.92 (mean = 46.47). The mean time to diagnosis of PA since HT was 78.85 months (range of 1 to 295 months). The mean of potassium level was 3.0 (2.1 to 3.8) mEq/dL. The prevalence of co-morbidities were as follow diabetes/ impair fasting glucose 30%, dyslipidemia 30%, chronic kidney disease 20%, obesity 15%. The aldosterone to rennin ratio (ARR) was 16.56 - 282.5 ng/mL to ng/mL/hr. The abnormalities of adrenal gland were demonstrated by CT with seven cases of unilateral macroadenoma, five cases of adrenal limb thickening, three cases of unilateral microadenomas. Medical or surgical treatment significantly resulted in improved hypokalemia and hypertension. Five cases underwent adrenalectomy and the others were treated by antihypertensive medication especially aldosterone antagonist. There were four cases that still require potassium replacement eventually at lower dosage. Conclusion : The prevalence of primary aldosteronism at Prapokklao hospital was 0.15% which extremely lower than that of the reviewed literatures. The most important clue that triggered the investigation was ‘hypertension with hypokalemia’. The screening scheme might have to be initiated earlier, before patients present an obvious clinical of hypokalemia to include more cases.